Formation model for university teachers’ monitoring skills - Fakrutdinova, Guzaliya Zh.; Baubekova, Gulzamira D.; Irgebaeva, Nazilya M.; Fakhrutdinov, Bulat I.; Yureva, Oksana V.; Nikitina, Svetlana E. (Universidade Estadual Paulista, Faculdade de Ciências e Letras de Araraquara, 2021)
The problem relevance that we are studying is attributable to the need to create educational process monitoring at universities and the insufficient development of theoretical, scientific and methodological features of forming teachers’ monitoring skills in the course of their educational activities. The major aim of the study is to build a model for the formation of teachers’ monitoring skills of and its implementation into the universities’ educational process in Kazakhstan. The research methods include modeling which will allow to study this issue as a process of meaningful acquisition of university monitoring skills by teachers. The research results in this article represent a model for the formation of university teachers’ monitoring skills, show the properties of monitoring skills; develop a mechanism for introducing this model into practice. The practical significance of this article is that the model is aimed at adapting teachers to modern circumstances of professional activity in the educational sphere and is concentrated upon developing scientific and methodological support for education quality monitoring.